THE ROLE OF OPERATIONAL UNITS OF THE NATIONAL POLICE IN PREVENTING CYBERCRIME IN THE CONTEXT OF ECONOMIC GLOBALISATION AND EXISTENTIAL CHALLENGES - Viacheslav Davydenko; Anna Kavunska; Viacheslav Barba (Baltic Journal of Economic Studies)
The study focuses on the conceptual, theoretical, empirical and methodological foundations of a legal and economic nature, concerning the legal support for the activities of operational units of the National Police in preventing cybercrime, in the context of economic globalisation and existential challenges. Methodology. The present study employed both general and special methods of cognition. Utilising the dialectical method, the author evaluated the essence of countering cybercrime by operational police units in terms of its prevention and prevention of these offences in the legal and economic planes, according to a diverse range of parameters. The analysis established the foundations for a multidimensional study of all the characteristic features of cybercrime prevention in the context of economic integration, in terms of economic and legal etymology. The synthesis established the conditions necessary for the generalisation of the distinctive features of the activities of police operational units. The formal legal method enabled the correct interpretation of the content of legal acts defining the general and special legal regimes of preventive activities of operational police units within the context of economic globalisation and existential challenges. The purpose of the article is to provide a comprehensive analysis of the potential areas for improvement in the activities of the operational units of the National Police in order to prevent cybercrime in the context of economic globalisation and existential challenges. The results of the study demonstrated that the role of the operational units of the National Police in preventing cybercrime in the context of economic globalisation and existential challenges encompasses a range of complex measures in various areas of activity of the relevant police unit, primarily in ensuring cybersecurity. It has been determined that there are specific areas in which the operational units of the National Police can enhance their efforts to combat cybercrime. These areas have been identified in the context of economic globalisation and existential challenges. Conclusion. The advent of cybercrime can be attributed to the prevailing technological transformations in the economy, particularly with regard to the dissemination of information as the primary resource and catalyst for societal advancement. The author's position is that the implementation of economic policies aimed at curbing cybercrime should encompass the following measures: the establishment of a fair and balanced tax system, the formulation of a strategic economic development policy, the promotion of production-oriented initiatives, and the allocation of resources towards the enhancement of public services. From the standpoint of a company's economic security, measures to prevent cybercrime are crucial, due to both local and global economic factors. The analysis of cybercrime legislation enabled the identification of measures of general and special competence taken by the operational units of the National Police. Concurrently, within the legislative framework on national security, which encompasses cybersecurity, the National Police is delineated as a subject of counteraction to such crime, signifying a specialised competence. Concomitantly, the general competence in combating and preventing cybercrime is reflected in the primary function of the National Police, namely to ensure public safety and order, protect human rights and freedoms, the interests of society and the state, and combat crime, including in cyberspace. The primary focus of the implementation of the special competence of operational police units is the Cyber Police Department, which is an integral component of the National Police. The Cyber Police Department is responsible for conducting comprehensive operational and investigative activities as a component of the broader strategy to prevent cybercrime. The authors support the view that the following measures, carried out by operational police units, stand out as effective means of countering cybercrime under conditions of existential challenges associated with armed aggression. These measures include counterintelligence, operational and investigative work, and procedural work to counter relevant information threats; the introduction of incentive measures aimed at creating their own information product; the development of their own information and telecommunications infrastructure; and the establishment of communication between civil society and law enforcement agencies in this area.